Venture capital healthcare investments and health care sector growth: A panel data analysis of Europe - Fauna Atta Frimpong; Ellis Kofi Akwaa-Sekyi; Ramon Saladrigues (Borsa Istanbul Review, 2022)
We examine the effect of venture capital investments on health sector growth, using a macro sample data from EVCA (now Invest Europe), World Bank, OECD and Eurostat databases covering 23 EU/EEA countries between 2000 and 2019. We follow the system GLS fixed effect and random effect approach, posit and find evidence that VC healthcare investments and age of VC industry increase healthcare sector growth in Europe. Life expectancy (one of the proxy variables for health sector growth) shows increasing trends in Europe. We also find that innovation, financial sector development, macroeconomic variables and healthcare infrastructure significantly increase health sector growth. We conjecture that VC investors may enjoy returns on investments which decipher into social returns to health sector outcomes. Our study makes justification for private-public partnership to support health sector growth. We recommend more funding support and inducement policy models tailor-made to reap benefits from overall health sector growth.